2015
DOI: 10.1097/tp.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in Patients With Cirrhosis of the Liver and Posttransplant Outcomes

Abstract: Cryptococcosis in patients with cirrhosis has grave prognosis. Our findings suggest that transplantation after recent cryptococcal disease may not be a categorical exclusion and may be cautiously undertaken in liver transplant candidates who are otherwise deemed clinically stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Of the 26 deaths, 24 (92%) were attributed to Cryptococcus [ 5 ]. In a recent multicenter analysis of patients with cirrhosis and liver transplant, a mortality of 57.1% was observed [ 15 ]. End-stage liver disease was associated with a 7.5-fold increase in unsatisfactory outcomes amongst patients infected with hepatitis B in China [ 16 ] and a 100% mortality in a small Taiwanese cohort of 33 HIV-negative patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 deaths, 24 (92%) were attributed to Cryptococcus [ 5 ]. In a recent multicenter analysis of patients with cirrhosis and liver transplant, a mortality of 57.1% was observed [ 15 ]. End-stage liver disease was associated with a 7.5-fold increase in unsatisfactory outcomes amongst patients infected with hepatitis B in China [ 16 ] and a 100% mortality in a small Taiwanese cohort of 33 HIV-negative patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of 112 cirrhotic patients with CD demonstrated lower mortality in the group that underwent transplant compared to those who did not. However, it is hard to determine if this differential outcome is because healthier patients were chosen for transplantation and does not examine how patients with CD fared compared to those without(27). It is important to note that treatment for CD with fluconazole will complicate the management of transplantation through drug-drug interactions with anti-rejection medications.…”
Section: Cryptococcosis In Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…One such group of patients are those with end-stage liver disease (ESLD)(27, 42). ESLD patients have a 5-fold higher rate of dissemination compared to other HIV-negative patients with CD(43).…”
Section: Cryptococcal Disease In Non-hiv Non-transplant Patientsmentioning
confidence: 99%
“…Cirrhosis has come to be recognized as a major risk factor for cryptococcosis [ 3 , 9 , 10 ]. Indeed, 21% to 36% of Cryptococcus infections in HIV-negative patients occur in patients with cirrhosis, and end-stage liver disease (ESLD) was the third most common predisposing factor for cryptococcosis after AIDS and iatrogenic immunosuppression [ 3 , 10 ].…”
Section: Cirrhosis-associated Cryptococcosismentioning
confidence: 99%
“…Cryptococcal disease in patients with ESLD presents as peritonitis (19%–45%), meningitis (39%–48%) and pulmonary disease (18%–37%) [ 9 , 14 ]. In addition, cryptococcemia and disseminated disease occur in 50% to 70% and 19% to 76% of patients with cirrhosis-related cryptococcosis, respectively, and are more likely to be associated with septic shock [ 3 , 9 , 10 , 14 ].…”
Section: Cirrhosis-associated Cryptococcosismentioning
confidence: 99%